Anonymous 2 (London, 2011)
2011 "Anonymous 2", 2011, HistoryTalk Anonymous 2 worked at Gillette's from 1965 to 1970 when he was made redundant but returned in 1985 and was made redundant a second time in 2003. He completed an apprenticeship at Evesham Vignells in 1965 and it was normal to go straight into a company following apprenticeship. Gillette's made electrical test equipment and he worked as a Prototype Wireman in the Research & Development Department. He also worked for a firm of launderettes, repairing machinery and plant and in a dry cleaning factory. Gillette's provided services for its staff like a medical centre and a dentist. The company created a social centre for staff.